Identification of gender using radiomorphometric measurements of canine by discriminant function analysis - Lakshmi Kavitha Nadendla; Geetha Paramkusam; Archana Pokala; Revath Vyas Devulapalli (Wolters Kluwer Medknow Publications, 2016)
Purpose: Human teeth are the most stable and durable tissues in the body. Teeth can be identified even after complete decomposition, thus making them invaluable for identification of sex and age from fragmentary adult skeleton. This study aimed to compare the morphological and radiological measurements of canine and investigate its accuracy in sex determination. Materials and Methods: This study involved 60 males and 60 females between the age group of 20 and 30 years. Mesiodistal (MD) widths of mandibular left canines and mandibular inter-canine distance (ICD) were measured and compared both clinically and on digital intraoral periapical and occlusal radiographs. Discriminant function analysis was carried out for gender determination. Discriminant equation and cutoff point were used in determining the gender and the percentage accuracy. Kappa statistics were carried out to assess intra-observer agreement. Results: A definite statistically significant difference in the MD width and ICD was found between males and females. Clinical and radiological measurements were almost equally efficacious in gender determination with an accuracy of 55-75% in both males and females. When all the variables were used, the accuracy of gender determination increased substantially to 94%. k-values suggested a high intra-observer agreement. Conclusion: It can be concluded that both the clinical and radiographic measurements of MD width of canine and ICD are quick and easy methods for determining sex and in identification of an unknown individual with a substantial accuracy.